Ecophysiology of horticultural crops: an overview (2010)
Horticultural crops include a wide range of commodities, such as fruits and vegetables that are highly valuable for humanity. They are extensively grown worldwide, and their production can be described as an open and highly complex system affected by many factors, among which we can count weather, soil and cropping system, as well as the interaction between these factors. The aim of environmental physiology is to characterize the interaction between environmental stress and crop response, in order to maximize both yield quantity and quality. This review presents the most recent findings about the effects of the main abiotic environmental factors (light, temperature, and water) on whole plant physiology of horticultural crops. Environmental stresses can cause morpho-anatomical, physiological and biochemical changes in crops, resulting in a strong profit reduction. A clear understanding of environmental factors and their interaction with physiological processes is extremely important for improving horticultural practices (irrigation, light management, mineral nutrition, greenhouse design, etc.), optimizing photosynthetic carbon assimilation and increasing fruit productivity and crop quality. In addition, the information obtained by ecophysiological studies can be incorporated into breeding programs or agricultural zoning strategies.